2009
DOI: 10.4103/0973-8258.59741
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study onin vitroandin vivoantioxidant activities of aqueous extract ofDesmodiumgangeticum(Leguminosae)root

Abstract: The present study was designed to investigate the in vitro and in vivo free radical scavenging effect of aqueous extract of Desmodium gangeticum (DG) root in different antioxidant models and experimentally induced ischemic reperfusion in an isolated rat heart. The rats were divided into three groups namely control, reperfusion control, and drug treated. For in vivo study, ischemic reperfusion injury (IRI) was induced by 30 minutes ischemia followed by reperfusion of Krebs-Henseleit buffer for 15 minutes or 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Associated with myocardial ischemia and reperfusion is the generation of oxygen-derived free radicals from a variety of sources that include the mitochondrial electron transport chain; the biosynthesis of prostaglandins; the enzyme xanthine oxidase; and circulating elements in the blood, with the polymorphonuclear neutrophil assuming a primary focus of attention. Studies have shown that Desmodium gangeticum possesses the ability to scavenge the free radicals generated during ischaemia and ischaemia reperfusion and thereby preserves the mitochondrial respiratory enzymes that eventually lead to cardioprotection (Kurian et al, 2005(Kurian et al, , 2008(Kurian et al, , 2009a(Kurian et al, ,b, 2010aPaddikkala, 2009, 2010).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Associated with myocardial ischemia and reperfusion is the generation of oxygen-derived free radicals from a variety of sources that include the mitochondrial electron transport chain; the biosynthesis of prostaglandins; the enzyme xanthine oxidase; and circulating elements in the blood, with the polymorphonuclear neutrophil assuming a primary focus of attention. Studies have shown that Desmodium gangeticum possesses the ability to scavenge the free radicals generated during ischaemia and ischaemia reperfusion and thereby preserves the mitochondrial respiratory enzymes that eventually lead to cardioprotection (Kurian et al, 2005(Kurian et al, , 2008(Kurian et al, , 2009a(Kurian et al, ,b, 2010aPaddikkala, 2009, 2010).…”
Section: Resultsmentioning
confidence: 97%
“…Studies were also focused on the in vivo free radical scavenging potential of aqueous extract of Desmodium gangeticum root by inducing oxidative stress in ischemic reperfused rat heart model (Kurian et al, 2009a). The observations suggested a potent antioxidant capacity for Desmodium gangeticum as compared to standard drug verapamil against revascularization injury.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have proved that D. gangeticum possessed antioxidant activity (Kurian et al, 2010;Kurian et al, 2009;Kurian & Paddikkala, 2009;Govindarajan et al, 2007;Govindarajan et al, 2003). In another study pretreatment of rats with aqueous extract of D. gangeticum orally for thirty days showed significantly improved preservation of antioxidant enzymes (SOD; CAT; GPX and glutathione reductase, GR) and subsequent reduction in LPO (Kurian & Paddikkala, 2009).…”
Section: Discussionmentioning
confidence: 98%